The effect of environmental, social, and governance (ESG) performance and capital structure on firm value in manufacturing companies listed on the Indonesia Stock Exchange for the 2019–2023 period - Putri, Aliea Yenemia; Sukmadilaga, Citra; Cempaka, Adisti Gilang (Universitas Padjadjaran, 2025)
This study aims to analyze the effect of Environmental, Social, and Governance (ESG) performance and capital structure on firm value in the manufacturing sector listed on the Indonesia Stock Exchange (IDX) for the period 2019–2023. ESG performance is measured using individual and combined scores from LSEG Datastream (Refinitiv). Capital structure is proxied by the Debt-to-Equity Ratio (DER), while firm value is measured using the Tobin’s Q ratio. This research adopts a quantitative approach using panel data regression analysis. The sample consists of 20 manufacturing firms selected through purposive sampling. Control variables include firm size, profitability (ROA), and macroeconomic factors such as stock return sensitivity to inflation, interest rate changes, and global oil price fluctuations. The results show that partially, both individual and combined ESG scores, as well as capital structure, do not significantly affect firm value. However, ESG performance and capital structure jointly have a significant effect on firm value.